Histopathological characteristics of dental socket healing on collagen density following use of pangas catfish (Pangasius djambal) gelatin - Fredy Mardiyantoro; Nenny Prasetyaningrum; Hani Tri Rahmastuti (Faculty of Dentistry, Universitas Gadjah Mada, 2019)
Tooth extraction is a common treatment in dental practice. However, complications such as bleeding or dry socket may occur during healing process. Pangas catfish (Pangasius djambal) gelatin contains glutamine which could increase the proliferation of fibroblast, accordingly collagen synthesis increases. The study aimed to demonstrate collagen density after the application of pangas catfish gelatin on post-tooth extraction wound of albino rats (Rattus norvegicus). This wasan experimental study with randomized posttest-only control group design which involved male Wistar strain albino rats. The rats were selected using a random sampling method and divided into four groups, namely day-3 control group (n=7),day-7 control group (n=7), day-3 treatment group (n=7) and day-7 treatment group (n=7). Pangas catfish gelatin was administered into the socket once after extraction. The variable measured in the study was collagen density, determinedby collagen scoring of hematoxylin eosin–stained histopathological preparations. Collagen formation were determined according to the assessment criteria of collagen distribution and density. Data analysis showed there was a significantdifference of collagen synthesis between the control and treatment groups according to Kruskal-Wallis test of which the result of control group day-3 was 1.13 ± 0.34, control group day-7 was 1.76 ± 0.67, treatment group day-3 was 1.66 ±0.47 and treatment group day-7 was 2.93 ± 0.25. In addition, the day-7 treatment group showed the highest collagen scoring values as compared to the control groups according to the Mann-Whitney test (p<0.05). In conclusion, pangascatfish gelatin increased collagen density during dental socket healing process after tooth extraction in albino rats.